(3GdJfTFI GdGLJeGYjI hGdLfSjI ddCHfGA GdeQGgbjf hGdTHGH ef GdLfSjf eSJNOej THcI GdGfJQfjJ, fehPL (B"(3HdOI GdUQafO (B- (3bVGA UjOG (B- (3LfhH dHfGfs - (3GdMGL, eQje MSfs ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3eYgO GdYdhe GdGLJeGYjIs, 2007)
(3JfGhdJ gPg GdOQGSI eSJNOej THcI GdCfJQfJ ef GdeQGgbjf hGdTHGH dWdGH GdeOGQS GdeJhSWI hGdKGfhjI GdQSejI hGdLGeYI GddHfGfjI dCHfGA GdCSQI aj HdOI GdUQafO bVGA UjOG, dHfGf GdLfhHj(B. (3EYJeOJ GdOQGSI Ydi efGgL YqOI(B: (3GdefgL GdGSJWdGYj GdGMUGFj dYjfI ef eQJGOj ebGgj GdGfJQfJ Mhd GSJNOGege ddTHcI, GdefgL GdhKGFbj, efgL GdJMdjd GdfhYj(B. (3ef Hjf GdJbfjGJ GdJj GSJNOeJ aj GdOQGSI(B/ (3GdedGMXI, GdebGHdI hGdGSJeGQI(B. (3Jqe JMOjO CSeGA WdGH HdOI GdUQafO GdPjf jJGHYhf OQGSGJge aj GdKGfhjI hGdeJhSWI GdQSejI hGdLGeYI GddHfGfjI hGdPjf JbY CYeGQge Vef GdaFGJ GdYeQjI (B14-23 (3SfI PchQG hEfGKG, hhbY GdGNJjGQ Ydi (B70 (3eSJNOeG(B. (3abO Jqe GSJWdGY CMhGd GdWdGH Yf cKH ef NdGd GSJeGQI eHGTQI, cTaJ YeG jJUaMhfg YHQ GdTHcI hhVYge GdCSQj GdGLJeGYj hGdJQHhj, hCYWJ ELGHGJ Yf WQjbI JYGWjge eY GdCfJQfJ, hJYGWj GdCgd eYge, eeG SGYO aj GdhUhd Edi cTa cjajI JYGWj hJYGed gDdGA GdeSJNOejf ddTHcI heOi GdJhGab ajeG jJdbhfg ef bje YHQ GdTHcI aj eLGdGJ GdJfTFI GdGLJeGYjI hGdLfSjI, hHjf eG fTChG Ydjg(B. (3ef Cge GdGSJfJGLGJ eG jdj(B: 1) (3hLhO eDTQ jfPQ HGdNWQ fGJL Yf ShA GSJNOGe GdTHcI HSHH JbUjQ GdCgd aj GdbjGe HhGLHGJge aj eLGd GdJfTFI GdGLJeGYjI hGdLfSjI, EP HdZJ fSHI YOe EecGfjI JMOK GdCHfGA eY GdCgd aj GdehGVjY GdLfSjI (B70%(3, hCOi HGdJGdj Edi HQhR eYGQa KbGajI CSGSjI dfeGPL bjejI LOjOI bO HOCJ HGdJcqhf dOi eSJNOej GdTHcI fGJL Yf GdMGLI ddEWdGY GdecKa Ydi GdeYQaI GdfXQjI GdeJfhYI, hHGdJGdj GdEWdGY Ydi bVGjG GdCehQ GdLfSjI hZjQ GdeCdhaI aj eLJeY GdOQGSI(B. 2) (3EVGaI Edi eSCdI JeVjI hbJ GdaQGZ, de jYO HGdTcd GdeCdha hGdeJYGQa Ydjg cGdeWGdYI hGdQMdGJ Hjf GdCUObGA, eLGdSI GdCgd hGdCbGQH, eeGQSI GdQjGVI(B... (3dJCNP efMi LOjOG hgh JaVjd GdLdhS CeGe THcI GdCfJQfJ HfSHI (B67.14%.s
(3GdfhY (B: (3QSGdIs
Keywords: Saida; South of Lebanon; (3LfhH dHfGfs; (3UjOGs; Adolescents; Adolescents; Education et la technologie; ICT and Education; Sarafand; Sarafand, Saida, Sud du Liban; Socialisation; Socialization; (3GdJYdje hGdJcfhdhLjGs; (3GdJfTFI GdGLJeGYjIs; (3GdUQafOs; (3GdeQGgbhfs